Production of Lactobacillus rhamnosus BRM 029693 in feed-batch fermentation (Research, Society and Development, 2020)
The objective of this work was to produce Lactobacillus rhamnosus BRM 029693 biomass in a fermenter with the aim to expand its production scale. Lactobacillus rhamnosus BRM 029693 was grown in a fermenter under different aeration conditions (in surface and depth) using a commercial substrate (MRS broth) and simplified substrate formulated in the laboratory itself, and under different pH conditions (4.7, 5.2, 5.7). The highest biomass production on a fermenter scale occurred using synthetic MRS, 1 v.v.m. aeration on the medium surface and without pH control (3.2 g/L) among all the tests. The biomass production was only 0.7 g/L when the MRS medium was replaced by simplified MRS. The pH also influenced the biomass production, reaching 0.9 g/L when the fermentation pH was controlled at pH 4.7.